Comparative study with scanning electron microscopy on the antennal sensilla of two main castes of Coptotermes formosanus Shiraki (Blattaria:Rhinotermitidae). (February 2020) - Fu, Bing-Xian; Rong, Nian-Hang; Hong, Jian; Zhu, Zeng-Rong; Mo, Jian-Chu; Zhang, Dayu
Highlights: Morphology, distribution and abundance of various types of sensilla was described. No obvious caste dimorphism was observed. Seven types of sensilla and a kind of small aperture were found. Functions of sensilla or structures were proposed. Abstract: Sensilla on antennae of the workers and soldiers of Coptotermes formosanus Shiraki were examined by scanning electron microscopy in this study. As the two castes were allocated totally different tasks in the termite colony, we wondered if there was a big difference between their antennae which were recognized as the main sensory appendages of insects. Therefore, detailed information about the morphology, distribution and abundance of various types of sensilla was described in this report. However, our results showed no obvious caste dimorphism was observed. The morphology of antennae and sensilla as well as the general sensilla distribution pattern did not differ between the workers and soldiers of C. formosanus . In total, seven types of sensilla including sensilla chaetica (I, II, III), Böhm bristles, sensilla campaniformia (I, II, III), sensilla trichodea, sensilla basiconica, sensilla trichodea curvata and sensilla capitula were found on the antennae. Additionally, small apertures were found scattered randomly in the antennal cuticle. Functions of these sensilla or structures were proposed to be mechanoreceptors, chemo-receptors, thermo-hygroreceptors, co2 -receptors etc. which probably play crucial roles in their various social behaviors.